A Combination Of Vein Of Galen Aneurysmal Malformation And Bovine Aortic Arch In Newborn: A Case Report - Krishna Deo Mandal; Kalpana Subedi; Unnati Amatya; Janak Pathak (Journal of Nepal Medical Association)
Vein of Galen aneurysmal malformation is a rare intracranial arteriovenous malformation, coexistence with aortic arch anomalies is even more uncommon, carry high risk of morbidity and mortality related to endovascular procedure and poor neurological outcome. Vein of Galen aneurysmal malformation is a dilated venous pouch, a persistence of the embryonic median prosencephalic vein of Markowski. Often presents with high output cardiac failure, severe pulmonary hypertension, and systemic steal leading to hemodynamic compromise and multi organ failure. Bicêtre score scale determines the potential treatment option and prognosis of the disease. Aim of the medical treatment is initial stabilization of life threatening condition of severe heart failure followed by the definitive treatment with endovascular embolization. Treatment is a big challenge, specially if coexistence with aortic arch anomalies which increases the morbidity and mortality. We describe a term neonate found to have vein of Galen aneurysmal malformation associated with bovine aortic arch.